2008
DOI: 10.1007/s12031-008-9134-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Extracellular Signal-Regulated Protein Kinase is Associated with Colorectal Distension-Induced Spinal and Supraspinal Neuronal Response and Neonatal Maternal Separation-Induced Visceral Hyperalgesia in Rats

Abstract: The activation of extracellular signal-regulated protein kinase (ERK) is essential for pain sensation and development of hyperalgesia in chronic pathological pain. Neonatal maternal separation (NMS) could trigger behavioral hyperalgesia and upregulate central neuronal activity in rats. The present study aims to investigate whether ERK associates with the colorectal distension (CRD)-evoked neuronal response and the upregulated central sensitivity to CRD in NMS rats. Male Sprague-Dawley rat pups were either subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 53 publications
3
24
0
Order By: Relevance
“…In previous studies, we found that NMS rats developed visceral hyperalgesia and enhanced neuronal sensitivity to noxious visceral stimuli in the central brain nuclei [4,5] . These nuclei, including the cingulate cortex, the thalamus and the amygdala, play important roles in the central pain matrix and are involved in generating emotional and autonomic responses [6,7] .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In previous studies, we found that NMS rats developed visceral hyperalgesia and enhanced neuronal sensitivity to noxious visceral stimuli in the central brain nuclei [4,5] . These nuclei, including the cingulate cortex, the thalamus and the amygdala, play important roles in the central pain matrix and are involved in generating emotional and autonomic responses [6,7] .…”
Section: Introductionmentioning
confidence: 84%
“…The increased excitability in response to visceral stimuli in the spinal cord after NMS, observed in our previous studies [4,24] , reflects changes in plasticity in descending pain circuitry. Our recent work has shown differential regulation of phospho (p)-Erk and c-Fos expression in the central pain matrix [5] . However, the mechanisms underlying these changes in plasticity are unknown.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Retrograde tracing studies in rat (Peschanski and Besson, 1984;Chen and Su, 1990;Otake et al, 1995;Novak et al, 2000;Krout et al, 2002) show that PVA receives projections from regions that are important in generating pain perception such as ACC, CeA, parabrachial area (PB), PAG, dorsal and medial raphe nucleus, and nucleus raphe magnus (Price, 2000;Millan, 2002). Although PVA is not commonly known as the pain matrix in the brain, increased c-Fos expression and pERK staining in PVA have been reported in several pain models in rat and mouse (Bullitt, 1990;Davies et al, 1997;Gioia et al, 2001;Chung et al, 2007;Nishii et al, 2008;Zhang et al, 2009). In the present study, pharmacological inactivation of ERK in PVA blocked the acid-induced chronic hyperalgesia in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, a similar number of c-Fos-positive neurons did not coexpress pERK1/2, indicating that alternative pathways such as protein kinase A, protein kinase C, and p38 kinase could also regulate c-Fos expression (Benavides et al, 2005;Svensson et al, 2005;Gonzá lez-Cuello et al, 2007). Regarding the association between ERK1/2 and c-Fos, some in vivo studies show that in the spinal cord, ERK1/2 is required for c-Fos expression after noxious stimulation (Cruz et al, 2007;Zhang et al, 2009), whereas others illustrate c-Fos expression in the absence of ERK1/2 activation in different animal models (Ji and Rupp, 1997;Kominato et al, 2003).…”
Section: Downloaded Frommentioning
confidence: 99%